Chattering analysis of an optimized sliding mode controller for an electro-hydraulic actuator system - Ghazali, Rozaimi; Chong, Chee Soon; Ghani, Muhamad Fadli; Chai, Mau Shern; Md. Sam, Yahaya; Has, Zulfatman (Department of Electrical Engineering, Universitas Muhammadiyah Yogyakarta, 2022)
Wear and tear are usually caused by various factors, which reduce the life span of a mechanical part. In the control engineering of an electro-hydraulic actuator (EHA) system, the wear and tear can be caused by the system or the controller itself. This article mainly examines the chattering effect that occurs during the sliding mode controller (SMC) design and its effect on the nonlinear EHA system. To examine the chattering phenomenon, a signum function is first applied to the switching function of the SMC. Then, parameters of the controller are obtained using the particle swarm optimization (PSO) method through a single objective function. These parameters are then applied to the switching function with the hyperbolic tangent function. Lastly, the performances of both functions are analyzed and compared based on graph and numerical data. From the output data, the chattering phenomenon generated on the signum function is greatly eliminated by using the hyperbolic tangent function. Thus, it can be inferred that the performance of the SMC can be greatly enhanced by manipulating the formula of the switching function.